Therapeutic Potential of Ginsenosides in Anthracycline-Induced Cardiotoxicity - Rongrong Bai; Zhigao Zhao; Xing Han; Mingying Shang; Guangxue Liu; Feng Xu; Shaoqing Cai (Molecules)
Anthracyclines play an irreplaceable role in cancer treatment, although their clinical application is limited due to severe side effects such as arrhythmia, cardiomyopathy, and myocardial infarction. The currently available clinical drugs for treating anthracycline-induced cardiotoxicity (AIC) are limited by numerous drawbacks, including the side effects of the therapeutic agents, single treatment mechanisms, and individual patient variations. Therefore, novel drugs with broader applicability and multitarget synergistic protective effects are, therefore, urgently needed. Ginsenosides, the primary bioactive constituents of plants belonging to the genus Panax (family Araliaceae), exhibit a wide range of pharmacological activities, including anti-inflammatory, antioxidative, and antitumor effects, and have demonstrated cardioprotective properties against AIC. This article examines the mechanisms of AIC and the modulatory effects of ginsenosides on these mechanisms. This review highlights the potential molecular targets and signaling pathways through which ginsenosides exert therapeutic effects on AIC, including the regulation of oxidative-stress-related pathways such as Keap1/Nrf2, MAPK, STAT, PI3K/Akt, and AMPK; the restoration of mitochondrial function; the modulation of autophagy; and the inhibition of pyroptosis, ferroptosis, and apoptosis. Therefore, this review serves as a theoretical basis and provides a research direction for future investigation regarding the prevention and treatment of AIC with ginsenosides, as well as clinical translation studies.